Analisis Kebutuhan dalam Pengembangan Bahasa Asing dI UIN Imam Bonjol Padang - Asrina Asrina; Abdul Manan Sihombing (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Learning foreign languages, especially Arabic and English at the Imam Bonjol State Islamic University in Padang has been going on for a long time but the results have not been as expected and are seen as not satisfying stakeholders. For this reason, it is necessary to conduct research on the programs that are run based on the need analysis for training foreign languages. Need analysis is the process of finding gaps between what people know, do, or feel and what they have to know, do, or feel in order to be able to do competently. Therefore, needs analysis is planned and carried out to obtain a number of data or information about conditions and needs. Needs analysis helps organizations and individuals to find solutions. Needs analysis is needed before implementing the program to see gaps or differences between ideal and optimal conditions. The results of the needs analysis inspire the design of the type of program, the objectives and indicators of success, the structure of the program, the material, the evaluation and monitoring system, and the criteria for the participants and relevant resource persons. Through this research, Present Situation Analysis, Target Situation Analysis and Expected Improvements were carried out. From the analysis carried out it can be concluded that the foreign language training that has been conducted has not yet fulfilled expectations and has not been maximized, therefore comprehensive improvements need to be carried out from various sides.